Water Meters - Selection, Installation, Testing, and Maintenance - Manual of Water Supply Practices, M6 (4th Edition) (American Water Works Association (AWWA), 1999)
Annotation A guide to selecting, installing, testing, and maintaining water meters. Coverage includes selecting meter types, impacts on service adequacy, meter installation, testing of meters, and maintenance and repair of displacement meters. Also discusses shop layout and equipment, records, and remote registration. Includes a list of AWWA manuals. This manual discusses recommended practices; it is not an AWWA standard calling for compliance with certain specifications. Can be used by new and existing utilities of all sizes, and by design engineers and consultants. Member price $40.00. Annotation copyrighted by Book News, Inc., Portland, OR.
Title from content provider.
Keywords: elektronické knihy; electronic books